Measuring level of reflective thinking of physics pre-service teachers using effective essay argumentation. Issue 4 (3rd July 2020) - Rosmiati, Rosmiati; Liliasari, Liliasari; Tjasyono, Bayong; Ramalis, Taufik Ramlan; Satriawan, Muhammad
ABSTRACT: This study aims to analyze the reflective thinking skills of pre-service physics teachers on the subject of ocean climate. Respondents used were 73 pre-service physics teachers who were taking courses in earth and space science at one of the universities in the city of Bandung, Indonesia. Respondents were divided into two classes, namely experiment class 1 which was given worksheets based on prediction using structured argumentation essays (by determining claims, warranties, and backing) while experimental group 2 was given worksheets based on prediction-argumentation using freelance argumentation essays (unstructured). Data measurements were performed with 10 multiple choice questions and 5 reflective thinking essay questions and 4 worksheets. Data analysis was performed by comparing and testing the effects of using a t-test and calculating N-Gain in each class and descriptive data analysis worksheet. Based on the results of data analysis that the experimental class 1 has a much better reflective thinking ability than the experimental class 2. The use of structured worksheets greatly helps students in arguing which has an impact on increasing the reflective thinking abilities of pre-service physics teachers.